Basic residues in the T-cell receptor ζ cytoplasmic domain mediate membrane association and modulate signaling. - Zhang, H; Cordoba, S; Dushek, O; Van Der Merwe, P (2011)
The T-cell receptor (TCR) consists of a TCRαβ heterodimer, a TCRζ homodimer, and CD3γε and CD3δε heterodimers. The precise mechanism of T-cell triggering following TCR ligand engagement remains elusive. Previous studies reported that the cytoplasmic tail of CD3ε binds to the plasma membrane through a basic residue-rich stretch (BRS) and proposed that dissociation from the membrane is required for phosphorylation thereof. In this report we show that BRS motifs within the cytoplasmic tail of TCRζ mediate association with the plasma membrane and that TCR engagement results in TCRζ dissociation from the membrane. This dissociation requires phosphorylation of the TCRζ immunoreceptor tyrosine-based activation motifs by lymphocyte cell-specificprotein tyrosine kinase (Lck) but not ζ-chain-associated protein kinase 70 binding. Mutations of the TCRζ BRS motifs that disrupt this membrane association attenuate proximal and distal responses induced by TCR engagement. These mutations appear to alter the localization of TCRζ with respect to Lck as well as the mobility of the TCR complex. This study reveals that tyrosine phosphorylation of the TCRζ cytoplasmic domain regulates its association with the plasma membrane and highlights the functional importance of TCRζ BRS motifs.